Regulation of body weight and food intake by AGRP neurons during opioid dependence and abstinence in mice - Laing, Brenton T.; Jayan, Aishwarya; Erbaugh, Lydia J.; Park, Anika S.; Wilson, Danielle J.; Aponte, Yeka (Frontiers in Neural Circuits, 2022)
Dysregulation of body weight maintenance and opioid dependence are often treated as independent disorders. Here, we assessed the effects of both acute and long-term administration of morphine with and without chemogenetic activation of agouti-related peptide (AGRP)-expressing neurons in the arcuate nucleus (ARC-AGRP neurons) to elucidate whether morphine and neuronal activation affect feeding behavior and body weight. First, we characterized interactions of opioids and energy deficit in wild-type mice. We observed that opioid administration attenuated both fasting-induced refeeding and ghrelin-stimulated feeding. Moreover, antagonism of opioid receptors blocked fasting-induced refeeding behavior. Next, we interfaced chemogenetics with opioid dependence. For chemogenetic experiments of ARC-AGRP neurons, we conducted a priori behavioral qualification and post-mortem FOS immunostaining verification of arcuate activation following ARC-AGRP chemogenetic activation. We administered clozapine during short-term and long-term morphine administration paradigms to determine the effects of dependence on food intake and body weight. We found that morphine occluded feeding behavior characteristic of chemogenetic activation of ARC-AGRP neurons. Notably, activation of ARC-AGRP neurons attenuated opioid-induced weight loss but did not evoke weight gain during opioid dependence. Consistent with these findings, we observed that morphine administration did not block fasting-induced activation of the ARC. Together, these results highlight the strength of opioidergic effects on body weight maintenance and demonstrate the utility of ARC-AGRP neuron manipulations as a lever to influence energy balance throughout the development of opioid dependence.